Spanish seamen : memorandum of interview, with Jose I. de Lizaso - Lizaso, Jose I. de; Tewson, Vincent
025a-0109-001 MEMORANDUM OF INTERVIEW. Date 27th April, 1939. Reference HVT/FC/458. Time 3.45 p.m to SUBJECT. SPANISH SEAMEN. Present Senor Lizaso. Mr. H. V. Tewson. Senor Liaaso called to enquire what progress had been made in connection with our request to the National Union of Seamen that they should consider whether it would be possible to accept a number of Spanish sailors on British ships. I informed Senor Lizaso that the reply of the Seamen had been in the negative, a policy which had been determined by the unemployment problem which they had and the difficulty of maintaining their policy of British seamen for British ships. Senor Lizaso then enquired as to whether there was any possibility of an arrangement being made whereby the Government could utilise the services of the Basque sailors for any purpose in an emergency. He referred to the fact that there were many Spanish sailors at Bizerte (Tunis) who were in a desperate plight, and he wondered whether anything could be done for them. I said it was very much doubted whether the Government would do anything in respect of sailors on French territory. He then raised a further point and said that sixteen men from Newcastle had secured employment on the Panama Line and enquired as to whether anything could be done in order to get the Spanish sailors on board foreign ships if it were not possible to get them on British ships. He understood that there were certain agents who were responsible for placing sailors and that in the case of Newcastle the agents received £2 per man. In regard to emigration Senor Lizaso undertook to make enquiries in regard to the desires of Spanish seamen in this country with respect to emigration and to communicate with the Spanish Committee in Paris on the possibility of some of them being included in the scheme of emigration to North or South America. He said that the Basque Delegation had received some money from the Atlantic Shipping Company who had been acting as agents for the Spanish Republican Government and he desired that the greater portion of this money should be administered by us in connection with the relief of the Spanish sailors. He also intimated that the Basque Delegation was assisting seamen in proceedings against the proprietors of Spanish ships in regard to wages due, and in connection with this matter the proposal was that from any monies received £20 of the proceeds should be deducted in order to provide a fund for contesting the remaining cases. He said that they had secured favourable findings in two cases, but that the Spanish proprietors had not yet paid up. 292/946/25a/109